2020
DOI: 10.1016/j.clae.2020.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Silicone hydrogel daily disposable benefits: The evidence

Abstract: Daily disposable (DD) contact lenses first came to the market approximately 25 years ago and eye care professionals (ECPs) started prescribing silicone hydrogel (SiH) contact lenses, primarily for extended or continuous wear, approximately 20 years ago. It has now been over ten years since SiH DD contact lenses have been available, and while SiH materials are routinely prescribed by ECPs for reusable daily wear, hydrogel materials are still frequently selected for the DD modality of contact lens wear. This art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 119 publications
(165 reference statements)
0
24
0
1
Order By: Relevance
“…As access to clinical care might continue to be limited over the coming months, ECPs are encouraged to review patient education on safe contact lens wear and care to minimise the chance of contact lens related complications. Daily disposables offer an advantage over reusable lenses in terms of non-compliance with cleaning and care procedures (relying on optimal handwashing only) [ [30] , [31] ]. Nagra et al [ 32 ] highlight that aftercare appointments had traditionally offered an ideal opportunity to assess contact lens compliance, but in the current times ECPs are encouraged to also use alternative ways (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As access to clinical care might continue to be limited over the coming months, ECPs are encouraged to review patient education on safe contact lens wear and care to minimise the chance of contact lens related complications. Daily disposables offer an advantage over reusable lenses in terms of non-compliance with cleaning and care procedures (relying on optimal handwashing only) [ [30] , [31] ]. Nagra et al [ 32 ] highlight that aftercare appointments had traditionally offered an ideal opportunity to assess contact lens compliance, but in the current times ECPs are encouraged to also use alternative ways (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…As access to clinical care might continue to be limited over the coming months, ECPs are encouraged to review patient education on safe contact lens wear and care to minimise the chance of contact lens related complications. Daily disposables offer an advantage over reusable lenses in terms of noncompliance with cleaning and care procedures (relying on optimal handwashing only)[30][31].…”
mentioning
confidence: 99%
“…Daily disposable contact lenses have gained popularity since their inception because of the many benefits of a daily disposable contact lenses such as ease of use and increased compliance due to the limited need for contact lens care products like multipurpose solutions or cases. [31][32][33] Therefore, it seems prudent to investigate whether this simplified modality has influenced the frequency of contact lens dropout.…”
Section: Wear Schedulementioning
confidence: 99%
“…We read with great interest the publication 'Silicone hydrogel daily disposable benefits: The evidence' [1].…”
mentioning
confidence: 99%
“…The study cited by the authors that shows similar comfort in SiHy DDs and hydrogel DDs includes etafilcon A, a hydrogel material that remains the number one daily disposable contact lens brand globally. 1 With the current research literature supporting little difference in comfort performance between SiHy DD and Hydrogel DD lenses, the authors refer to the results of a market research survey that reported ECP perceptions. The publication of this survey reported that ECPs believe that SiHy DDs are more comfortable [10], but the authors of this work acknowledged the survey questions were phrased with an emphasis on SiHy materials and their possible benefits over hydrogels and included the results for 'slight agreement' with the statement, so potentially increasing the percentages significantly as there was no neutral response in the questionnaire.…”
mentioning
confidence: 99%